Distributed fault-tolerant consensus tracking control for multi-agent systems under multiple attacks: An encoding–decoding strategy - Liu, Yiliu; Liu, Chun; Ren, Xiaoqiang; Lan, Jianglin; Wang, Xiaofan (Chaos, solitons and fractals, 2025)
This study investigates the distributed fault-tolerant consensus tracking (FCT) problem of multi-agent systems (MASs) subject to actuator faults, and deception and eavesdropping attacks. The problem is addressed through the proposal of a unified framework that integrates decentralized high-gain estimator-based (HGE) estimation, encoding–decoding strategy-based (EDS) encryption–decryption, and distributed fault-tolerant consensus tracking control (FCTC). The decentralized HGE simultaneously estimates system states, actuator faults, and deception attacks, while mitigating the impact of deception attacks on the estimation. The EDS encrypts and decrypts the estimated state and/or alleviates communication congestion. The distributed FCT controller, incorporating fault estimation and state encryption, achieves compensation for faults and maintains data confidentiality against eavesdropping attacks. Rigorous analysis establishes sufficient conditions that guarantee leader-following consensus with uniform ultimate boundedness. The communication data size is explicitly analyzed as a performance metric, revealing the intrinsic trade-off between tracking accuracy and communication efficiency. Simulation studies under various faults/attacks scenarios validate the effectiveness of the proposed framework. •The control protocol combines privacy preservation and fault tolerance.•The estimator, encoding–decoding strategy, and controller are co-designed.